2021
DOI: 10.1371/journal.pone.0247411
|View full text |Cite
|
Sign up to set email alerts
|

Closing delivery gaps in the treatment of tuberculosis infection: Lessons from implementation research in Peru

Abstract: Background Targeted testing and treatment of TB infection to prevent disease is a pillar of TB elimination. Despite recent global commitments to greatly expand access to preventive treatment for TB infection, there remains a lack of research on how best to expand preventive treatment programs in settings with high TB burdens. Methods We conducted implementation research in Lima, Peru, around a multifaceted intervention to deliver TB preventive treatment to close contacts of all ages, health care workers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…This compares favourably to the 20%–53% who completed contact investigation in prior studies, and the number needed to screen of 13 was far below the 56 reported in a prior systematic review 34 35 49 50. Nevertheless, over half of child contacts eligible for TPT did not start it, similar to results reported elsewhere,50–52 and the likelihood of initiation decreased substantially with increasing age of index patients. In a prior systematic review,36 a low perceived risk of active TB for one’s children was among the most frequent reasons for low uptake, emphasising the need for personalised education and counselling to address parental concerns.…”
Section: Discussionsupporting
confidence: 74%
“…This compares favourably to the 20%–53% who completed contact investigation in prior studies, and the number needed to screen of 13 was far below the 56 reported in a prior systematic review 34 35 49 50. Nevertheless, over half of child contacts eligible for TPT did not start it, similar to results reported elsewhere,50–52 and the likelihood of initiation decreased substantially with increasing age of index patients. In a prior systematic review,36 a low perceived risk of active TB for one’s children was among the most frequent reasons for low uptake, emphasising the need for personalised education and counselling to address parental concerns.…”
Section: Discussionsupporting
confidence: 74%
“…By the time a diagnosis is made, household contacts have already been exposed to the patient’s infection, and the likelihood of contact infection decreases rapidly when treatment is initiated. Even in cases of patients who have MDR-TB or XDR-TB, community-based treatment models have been successfully implemented in a variety of settings [ 150 - 152 ]. - Isolation or detention should be limited to exceptional circumstances when the patient is: contagious, and refuses treatment and all reasonable measures to achieve compliance have been attempted with unsuccessful outcome.…”
Section: What Obligations and Legal Implications Are Associated With ...mentioning
confidence: 99%
“…The TB care cascade has been identified as a framework for measuring the quality of TB care (Subbaraman et al, 2020). It includes case detection, contact detection, diagnosis, linkage to care, case retention, and post-treatment follow-up (Yuen et al, 2021) (Amisi et al, 2021). The cascade provides methods to quantify gaps in the TB cascade (Subbaraman et al, 2019).…”
Section: Yearmentioning
confidence: 99%